1986
DOI: 10.3928/0098-9134-19861001-07
|View full text |Cite
|
Sign up to set email alerts
|

The Realities of Body Image

Abstract: The older individual may have to make more adaptations to altered body image, especially in light of the American culture's emphasis on youth, beauty, and wholeness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…In general, findings suggesting a positive correlation between body appreciation and age appear more in line with the gerontology literature. Indeed, the decreased importance of appearance in favor of health and functionality (Baker&Gringart,2009;Deeny&Kirk-Smith,2000;Janelli, 1986;Reboussin et al, 2000), as well as women's diminished tendency to consider their looks as central to their overall selfworth as they grow older (Tiggemann & Lacey, 2009), are all indicators of a positive, rather than negative, shift in women's relationship to their body with age.…”
Section: The Influence Of Agingmentioning
confidence: 96%
“…In general, findings suggesting a positive correlation between body appreciation and age appear more in line with the gerontology literature. Indeed, the decreased importance of appearance in favor of health and functionality (Baker&Gringart,2009;Deeny&Kirk-Smith,2000;Janelli, 1986;Reboussin et al, 2000), as well as women's diminished tendency to consider their looks as central to their overall selfworth as they grow older (Tiggemann & Lacey, 2009), are all indicators of a positive, rather than negative, shift in women's relationship to their body with age.…”
Section: The Influence Of Agingmentioning
confidence: 96%
“…Previous research has suggested a number of factors that may influence the psychological outcome of disfiguring injury. People have different social influences at different ages (Janelli 1986) and women may be more sensitive than men in terms of psychological difficulty following disfigurement (Anderson & Maksud 1994, Newell 2000. The general health literature suggests that those at a lower socio-economic level are more affected by their health status (Marmot et al 1991), and it has also been found that the unemployed are at greater risk of developing psychological distress following acute injury (Joy et al 2000).…”
Section: Factors That May Influence Psychological Outcomesmentioning
confidence: 99%
“…Body image is the way our body appears to ourselves as a mental image (Janelli, 1986). Body image, like self-esteem, is often used interchangeably with self-concept, but does not have the same meaning.…”
Section: Closely Related Termsmentioning
confidence: 99%